2018
DOI: 10.1101/403469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An HIV-1 broadly neutralizing antibody from a clade C infected pediatric elite neutralizer potently neutralizes the contemporaneous and autologous evolving viruses

Abstract: Keywords 23 HIV-1, clade C, N332 supersite, plasma neutralization, pediatric HIV-1 bNAb, single B cell 24 sorting, elite neutralizer, SOSIP trimer, negative stain EM and 3D reconstruction 25 2 Abstract 26 27 Broadly neutralizing antibodies (bNAbs) have demonstrated protective effects against HIV-1 28 in primate studies and recent human clinical trials. Elite-neutralizers are potential candidates 29 for isolation of HIV-1 bNAbs and coexistence of bNAbs such as BG18 with neutralization 30 susceptible autologous … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…MPER, RSC3 and RSC3Δ371I/P363N ELISAs were performed as described previously (16). Briefly, 96 well ELISA plates (Corning, USA) were coated with 2 µg/ml of RSC3, and RSC3Δ371I/P363N proteins and MPER-B and MPER-C peptides overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…MPER, RSC3 and RSC3Δ371I/P363N ELISAs were performed as described previously (16). Briefly, 96 well ELISA plates (Corning, USA) were coated with 2 µg/ml of RSC3, and RSC3Δ371I/P363N proteins and MPER-B and MPER-C peptides overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…In HIV-1 infected children, plasma bnAbs arise earlier in infection, and show higher potency and breadth compared to adults [15][16][17][18][19] . We observed the presence of cross-neutralizing antibodies in HIV-1 clade C chronically infected children 19 and recently generated a bnAb AIIMS-P01 from an elite pediatric neutralizer AIIMS_330 20 . Further, in this cohort of chronically infected children, AIIMS_329 and AIIMS_330, a pair of identical twins, showed elite plasma neutralizing activity 21 .…”
mentioning
confidence: 98%
“…Studies undertaken in infants have, however, documented that HIV-1 infected infants develop potent plasma bnAbs as early as one-year post-infection 17,18 suggesting that an effective vaccine in infants may perhaps be able to trigger the immune system and elicit an early bnAb response thus providing an impetus to evaluate the antibody response in a cohort of perinatally infected infants. Moreover, the bnAbs isolated from infected children show features atypical of adult bnAbs suggesting that the factors governing bnAb induction in infants are distinct from those in adults 20,22 .…”
mentioning
confidence: 99%
“…All plasmids were used to transform STBL3 Escherichia coli cells, followed by plasmid purification using a Qiagen plasmid isolation kit (mini-prep). Purified plasmid (5 µg) of each infectious molecular clone was expressed by transfecting HEK293T cells (ATCC) using PEI-Max transfection reagent (Polysciences), and the HIV-1 global panel of pseudoviruses was generated as described elsewhere [8,14,30]. Virus-containing supernatant was harvested at 48 h post-transfection by centrifugation and filtered through a 0.45 µm filter.…”
Section: Generation Of Hiv-1 Infectious Molecular Clones and Envelopementioning
confidence: 99%
“…Interestingly, recent studies on HIV-1 specific immune responses have demonstrated the development of (cross-subtype) broadly neutralizing antibodies (bnAbs) in infected infants 1 year of age and understanding the responses in such infants will provide useful information towards vaccine design. Furthermore, it has been observed that select HIV-1 infected infants [12,13] and chronically infected children [9,[14][15][16][17] develop bnAb responses earlier, with higher potency and breadth than infected adults, suggesting that the pathways of eliciting antibody responses may differ between HIV-1 infected children and adults [7, 12-14, 16, 17].…”
Section: Introductionmentioning
confidence: 99%